2012
DOI: 10.1111/j.1654-109x.2012.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

PredictingEllenberg's soil moisture indicator value in theBavarianAlps using additive georegression

Abstract: Questions: Can forest site characteristics be used to predict Ellenberg indicator values for soil moisture? Which is the best averaged mean value for modelling? Does the distribution of soil moisture depend on spatial information? Location: Bavarian Alps, Germany.Methods: We used topographic, climatic and edaphic variables to model the mean soil moisture value as found on 1505 forest plots from the database WINALPecobase. All predictor variables were taken from area-wide geodata layers so that the model can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
(66 reference statements)
1
15
0
Order By: Relevance
“…Soil moisture also affects plant composition and productivity (Häring et al, 2013) and thus controls the quantity and quality of both soil organic matter (SOM) and root exudate supply (Rustad et al, 2000).…”
Section: T Chang Et Al: Soil Moisture Overrules Temperature Depementioning
confidence: 99%
“…Soil moisture also affects plant composition and productivity (Häring et al, 2013) and thus controls the quantity and quality of both soil organic matter (SOM) and root exudate supply (Rustad et al, 2000).…”
Section: T Chang Et Al: Soil Moisture Overrules Temperature Depementioning
confidence: 99%
“…The increase in herb and moss projection cover could be a result of decrease in tree and shrub projection cover, thus allowing more sunlight to understorey vegetation. In forestry, bioindication with the mean values of EIVs has been used to assess the site productivity (Bergès et al, 2006) and to predict herb biomass production (Axmanová et al, 2012), water relationships in soils (Häring et al, 2013) and atmospheric deposition (Dobben et al, 1999). Some studies suggest that bioindication can perform better than instrumental measurements and predicts plant species occurrence more accurately (Dupré & Diekmann, 1998;Jarvis et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Häring et al. (), who made a spatial prediction of mF for the Bavarian Alps, showed that the moisture value must be modelled using a combination of predictors. In floodplains we are dealing with an interplay between hydromorphic processes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Ellenberg moisture value is a good indicator for hydrological conditions (Häring et al. ) and ecological change, but limitations do exist, as described in detail in Diekmann () and Ellenberg et al. ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation